Local Wisdom and Religious Values: An Analysis of Dakwah In Songkok Guru Craft Practices - Hamiruddin Hamiruddin; Irwan Misbach (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study examines the integration of da’wah values in the production practices of Songkok Guru as a representation of local wisdom within the creative economy. The objective is to analyze the production process and identify the internalization of aqidah, sharia, and akhlaq values in the daily activities of artisans. A qualitative descriptive approach is employed, using in-depth interviews, participant observation, and documentation to obtain contextual empirical data. Data analysis is conducted through iterative processes of reduction, display, and conclusion drawing, supported by triangulation to ensure validity. The findings reveal that the production of Songkok Guru embodies non-verbal da’wah through everyday work practices. Aqidah values are reflected in spiritual awareness and reliance on Allah swt, sharia values are manifested in cooperation and collective responsibility, while akhlaq emerges as the dominant dimension shaping character and work ethics. The production process not only generates economic products but also constructs religious habitus and value-based social systems that strengthen collective identity. The integration of religious values within the creative economy enhances product quality, consumer trust, and business sustainability. The study concludes that cultural production serves as an effective, contextual, and adaptive medium of da'wah. The implications highlight the importance of developing culture-based da’wah models as strategies for sustainable social and economic transformation.